Microfluidic-based platform to mimic the in vivo peripheral administration of neurotropic nanoparticles. (December 2016) - Lopes, Cátia DF; Gomes, Carla P; Neto, Estrela; Sampaio, Paula; Aguiar, Paulo; Pêgo, Ana P
Aim: Propose a nanoparticle for neuron-targeted retrograde gene delivery and describe a microfluidic-based culture system to provide insight into vector performance and safety.Methods: Using compartmentalized neuron cultures we dissected nanoparticle bioactivity upon delivery taking advantage of (quantitative) bioimaging tools.Results: Targeted and nontargeted nanoparticles were internalized at axon terminals and retrogradely transported to cell bodies at similar average velocities but the former have shown an axonal flux 2.7-times superior to nontargeted nanoparticles, suggesting an improved cargo-transportation efficiency. The peripheral administration of nanoparticles to axon terminals is nontoxic as compared with their direct administration to the cell body or whole neuron.Conclusion: A neuron-targeted nanoparticle system was put forward. Microfluidic-based neuron cultures are proposed as a powerful tool to investigate nanoparticle bio-performance.